Principles of parallel programming - Lin, Calvin (Pearson/Addison Wesley, 2009)
This book is ideal for an upper-level undergraduate or master's level course, or for a professional programmer seeking an introduction to parallelism. The text supplies valuable, enduring information that will outlive the current hardware and software.